DEVELOPING ENGLISH LISTENING MATERIALS FOR THE TENTH GRADE STUDENTS OF MUSIC PERFORMING ART VOCATIONAL SCHOOL - Boy Atlaliust Simangunsong; Rita Suswati (Universitas Negeri Medan, 2016)
The aim of this study was to find out an appropriate English listening materials forthe Grade X students of music performing art vocational school. SekolahMenengah Kejuruan (SMK) or Vocational School is an institution where studentsare prepared to be work-ready after finishing their education in specific major.Music Performing Art is one of the major provided in Indonesia’s vocationalschool. By the fact that listening activities are often ignored by teachers and thatlistening is one of the test in the National Examination, then listening activities areconsidered important in English learning activity. However, the finding ofmaterials that provided for the Grade X students of Music Performing Art major atSMK Negeri 11 Medan shows that the listening materials provided in the textbookare not related to the students’ major, instead the materials are rather general andmore suitable for other major. Therefore, it is needed to develop the Englishlistening materials for the tenth grader of music performing art major. Small-ScaleResearch and Development (R&D) is the suitable method in developing thematerials. Based on the students’ needs analysis obtained from the questionnaireswhich responded by 64 students and interviews which involved 4 students, theresearcher found that 78.13% of the respondents assumed that the existingmaterials provided by the teachers are general, and further 93.75% expect amajor-related English listening materials. The materials are developed by addingsome musical terms, like music instruments, and topics related to musical field,like popular singer’s profile, as a step to meet the students’ needs. The experts’validation shows that the materials are appropriate and recommended to be used.Based on the result of the study, conclusion and suggestions are directed to theEnglish teachers in SMK Negeri 11 Medan, especially, and in other music majorvocational school, generally, who are expected to provide materials which arerelated to the students’ major, by doing so the students might have motivation inlearning English and to support their knowledge to be a professional musicians.